Study of the effect of exercise fatigue on the gut microbiota of boxers - Mei-hua, Su; Jia-Hui, Jin; Wen-Long, Ding; Jian-Ming, Chen; Yu-Fei, Qin; Jian-Hua, Chen (Frontiers in Microbiology, 2025)
ObjectiveTo explore the changes in gut microbiota in response to exercise fatigue, to provide a theoretical basis for the diagnosis and intervention of exercise fatigue.MethodsIn this study, 16S rRNA sequencing of feces from 17 youth boxers was performed before and after fatigue using the Illumina HiSeq platform. After denoising and OTU clustering of the raw sequencing data using the QIIME2 DADA2 analysis pipeline, differential microbiota were analyzed using R statistical software.ResultsASV clustering analysis revealed that 2,470 Amplicon Sequence Variants (ASVs) were common between pre-and post-exercise fatigue, while 8,321 ASVs were unique to pre-exercise and 6,341 ASVs were unique to post-exercise. There was no statistically significant difference in α-diversity and β-diversity between pre-and post-exercise fatigue, although a trend of decreasing diversity was observed. At the phylum level, the relative abundance of Firmicutes and Bacteroidetes decreased, while the abundance of Actinobacteria and Proteobacteria increased. Using LEfSe multilevel species difference discriminant analysis, a total of 12 specific phyla were identified (|LDA| > 2, p < 0.05), with the top three phyla ranked by relative abundance being Prevotella (p = 0.025), Corynebacterium (p = 0.038), and Lachnospira (p = 0.004). The relative abundance of Prevotella, Corynebacterium, and Lachnospiracae increased differently in response to exercise-induced fatigue. Prevotella, Corynebacteriales, Lachnospiraceae were positively correlated with creatine kinase, and Lachnospiraceae was positively correlated with RPE scale.ConclusionExercise-induced fatigue may produce specific changes to the gut microbiota that correlate with exercise-induced fatigue markers.